Sindrome delle lentiggini multiple o sindrome LEOPARD. - Bonifazi , E. (European Journal of Pediatric Dermatology, 2015)
Sindrome delle lentiggini multiple o sindrome LEOPARD (Lentigines, Electrocardiographic abnormalities, Ocular hypertelorism, Pulmonary stenosis, Abnormalities of the genitalia, Retardation of growth and Deafness).